Управління у сфері земельних відносин та надрокористування - Райнін, І. Л.; Rainin, I. L. (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 2 (73). - С. 116-126, 2016)
Проаналізовано адміністративно-правове забезпечення управління у сфері земельних відносин та надрокористування, розглянуто пропозиції з питань упорядкування компетенції та повноважень суб’єктів землекористування.

Administrative and legal guaranteeing of the administration in the sphere of land relations and subsoil use in Ukraine has been analyzed; propositions for regulating the competence and powers of the subjects of land use have been considered. It is stressed that the administration in the sphere of land relations and subsoil use is realized by the extensive network of authorized entities, including the central executive authorities and their local departments and agencies, and local selfgovernments, which are endowed with different amounts of general and special jurisdiction and powers. There are contradictions and inconsistencies within legal regulation of these administration entities, which are to be eliminated by the amendments and alterations to the current legislation and the adoption of a number of relevant subordinate legislation. It is emphasized that the administration in the sphere of land relations and subsoil use should be based on the principle of taking into account the indispensability of land as the main mean of production, as space-territorial basis of natural resources, social and industrial infrastructure, which should serve the whole Ukrainian nation.

Проанализировано административно-правовое обеспечение управления в сфере земельных отношений и недропользования, рассмотрены предложения по вопросам упорядочения компетенции и полномочий субъектов землепользования.
Administration in the sphere of land relations and subsoil use
Управление в сфере земельных отношений и недропользования
Райнін, І. Л. Управління у сфері земельних відносин та надрокористування / І. Л. Райнін // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 2. - С. 116-126.
Райнін І. Л. "Управління у сфері земельних відносин та надрокористування." Вісник Харківського національного університету внутрішніх справ 2 (2016): 116-126.
Rainin, I.L. (2016), “Administration in the sphere of land relations and subsoil use” [Upravlinnia u sferi zemelnykh vidnosyn ta nadrokorystuvannia], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 116-126.
Keywords: Земельне право. Аграрне право. Land Law. Agrarian Law. Земельное право. Аграрное право; Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; земельні відносини; надрокористування; управління; суб’єкти землекористування; повноваження; органи виконавчої влади; місцеве самоврядування; land relations; subsoil use; administration; subjects of land use; powers; executive power bodies; local self-government; земельные отношения; недропользование; управление; субъекты землепользования; полномочия; исполнительная власть; местное самоуправление